Development of an Adhesion Assay and Characterization of an Adhesion-Deficient Mutant of Pseudomonas fluorescens - DeFlaun, Mary F. (1990)
A sand column adhesion assay was developed which distinguishes the adhesion abilities of a number of pseudomonads isolated from fine sandy loam. Pseudomonas fluorescens Pf0-1 which adhered at >90% of the total cells added was subjected to transposon Tn5 insertion mutagenesis. From 2,500 Pf0-1::Tn5 mutants examined in the sand column assay, two adhesion-deficient Pf0-1 mutants showing <50% attachment were isolated. Marker exchange analysis of one of these mutants, Pf0-5, confirmed that the decreased adhesion was linked to the Tn5 insertion in the chromosome. The growth rate of Pf0-5 in enriched media and sterile soil was similar to that of the wild type; in minimal medium, however, Pf0-5 grew faster. In a soil column assay, less Pf0-5 than wild-type bacteria were recovered, suggesting a decreased ability to persist in soil. A 34-kilodalton major outer membrane protein present in the wild type was missing in Pf0-5. Transmission electron microscopy of the cell surface revealed that the wild-type possessed polar flagella which were absent in the mutant.